Patterns of anterior and posterior muscle chain interactions during high performance long-hang elements in gymnastics - von Laßberg, C.; Rapp, W.; Krug, J. (Journal of Electromyography and Kinesiology, 2014)
In a prior study with high level gymnasts we could demonstrate that the neuromuscular activation pattern during the "whip-like" leg acceleration phases (LAP) in accelerating movement sequences on high bar, primarily runs in a consecutive succession from the bar (punctum fixum) to the legs (punctum mobile). The current study presents how the neuromuscular activation is represented during movement sequences that immediately follow the LAP by the antagonist muscle chain to generate an effective transfer of momentum for performing specific elements, based on the energy generated by the preceding LAP. Thirteen high level gymnasts were assessed by surface electromyography during high performance elements on high bar and parallel bars. The results show that the neuromuscular succession runs primarily from punctum mobile towards punctum fixum for generating the transfer of momentum. Additionally, further principles of neuromuscular interactions between the anterior and posterior muscle chain during such movement sequences are presented. The findings complement the understanding of neuromuscular activation patterns during rotational movements around fixed axes and will help to form the basis of more direct and better teaching methods regarding earlier optimization and facilitation of the motor learning process concerning fundamental movement requirements.